PENINGKATAN HASIL BELAJAR IPAS MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN BOOK CREATOR DI KELAS V SD - Bella Santika; Arwin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students’ IPAS learning outcomes through theapplication of the Problem Based Learning (PBL) model assisted by Book Creatorin grade V of SDN 45 Teluk Panjang. The research employed a Classroom ActionResearch (CAR) design in two cycles, each consisting of planning,implementation, observation, and reflection stages. Data were collected throughobservation, interviews, documentation, and learning outcome tests. The resultsshowed a significant improvement in lesson planning, implementation, andstudents’ learning outcomes. The average score increased from 80 (B) in cycle I to91 (SB) in cycle II. Both teacher and student activities also improved from good tovery good. The application of the PBL model encouraged students to be moreactive, enhanced critical thinking and collaboration skills, and resulted in betterlearning performance. The integration of Book Creator as a learning media furtherincreased student engagement and motivation. It can be concluded that the use ofthe PBL model assisted by Book Creator is effective in improving IPAS learningoutcomes in elementary school.